Revisiting pro-3r attitude mediating effect of green packaging on consumer purchase intention - Elisabet Anisa Gita P; Angga Ariestya (Jurnal Komunikasi Profesional, 2022)
The company has currently started to develop eco-friendly innovation products. This is driven by one of the emerging environmental issues in Indonesia, specifically plastic waste. Theory Planned Behavior was used as a theoretical framework in this research and has been widely used in several previous researches to measure the attitude in influencing consumer purchase intention and the concept of MPR. This research was intended to evaluate the effect of green packaging on purchase intention in Aqua LIFE’s products mediated by pro-3R attitudes. The object of this research was the green packaging of Aqua Life products which is referred to as Danone Aqua’s Marketing Public Relations program innovation. This research was conducted in the metropolitan area of DKI Jakarta. The sample in this research was determined by utilizing the non-probability sampling method by means of a purposive sampling technique. Data were collected using an online questionnaire with a Likert scale (with a point scale: (1) strongly disagree to (5) strongly agree). The number of respondents in this research was amounted to 347 respondents. The data in this research were then analyzed using path analysis by means of structural equation modeling (SEM). The results showed that: (1) Green packaging had a significant effect on the pro-3R attitude of Aqua LIFE’s consumers; (2) Green packaging had a significant effect on the purchase intention of Aqua LIFE’s products; (3) The pro-3R attitude did not successfully mediate the effect of green packaging on purchase intention of Aqua LIFE’s products in DKI Jakarta City. Consequently, further research is highly recommended to raise the pro-3R attitude variable as a moderator variable, not as a mediator variable. Keywords: Marketing Public Relations, Green Packaging, Theory Planned Behavior, Purchase Intention, and Pro-3R Attitude Introduction